Positive and negative regulatory elements of chicken vitellogenin II gene characterized by in vitro transcription competition assays in a homologous system. - Vaccaro, M (1990)
A homologous in vitro transcription system was developed in which the cloned chicken vitellogenin II gene is faithfully transcribed by extracts prepared from chicken liver nuclei. The use of template deleted of its upstream region resulted in poor transcriptional efficiency, as did the use of extracts prepared from rooster liver, in which the gene is silent. The influence of individual cis elements was determined by transcription competition analysis. Oligonucleotides covering greater than 500 base pairs of the promoter region were used as competitor DNA in the in vitro reactions. Competition with an oligonucleotide covering part of the expression-specific DNase I hypersensitivity site B2, which contains a demethylation site, mCpG, at nucleotide position + 10, increased transcription of the gene, suggesting the binding of a repressor to this region. The enhancement of transcription was even more pronounced when the same oligonucleotide was methylated at the corresponding + 10 cytosine. Competition with oligonucleotides covering the TATA box, or the estrogen response element half-palindromic motif (GGTCA) at nucleotide positions -198 to -194, resulted in a large decrease in vitellogenin gene transcription, indicating that strongly activating factors bind to these regions. Competing oligonucleotides covering other GGTCA-containing motifs situated further upstream at nucleotide positions -292 to -288, -367 to -351, and -626 to -614 were increasingly less effective in inhibiting transcription. The results indicate that factors other than the estrogen receptor are involved in transcriptional activation of the vitellogenin II gene.